Factors Associated with Treatment Outcome of Shorter Treatment Regimen (STR) for MultiDrug-Resistant Tuberculosis (MDR-TB) - Perangin-angin, Gwanita Nawariantina; Sinaga, Bintang Yinke Magdalena; Siagian, Parluhutan; Eyanoer, Putri Chairani (TALENTA Publisher, Universitas Sumatera Utara, 2024)
ABSTRACT Background: Indonesia ranked 2nd around the world for TB cases with case population continue increasing. In 2018, Shorter Treatment Regimen (STR) was introduced as a new regimen for treating MDR-TB patient. The aim of this study is to determine factors associated with treatment outcome of MDR-TB patients treated with Shorter Treatment Regimen Methods: This is a descriptive-analytic study using cross sectional design which was conducted at Adam Malik Hospital Medan. Subject was 150 patients with drug-resistant Pulmonary TB at MDR-TB polyclinics according to inclusion and exclusion criteria Results: MDR-TB patients that treated with STR was mostly < 50 years old (65.2%) and 107 subjects (70.4%) were male. The majority of subjects with comorbidity were 94 subjects (61.8%); 43 subjects (28.3%) with DM, 5 subjects (3.3%) with CHF, 3 subjects (2.0%) with HIV, 1 subject (0.7%) with DM & CHF, and 1 subject (0.7%) with DM & HIV. When evaluated the patients treatment outcome, 47.4% were cured, 6.6% were failed, 34.8% were default and 11.2% were death. A chi square test was conducted to assess association between age with treatment outcome. Age was significantly associated with treatment outcome (p=0.038) but gender and comorbidity were not associated with treatment outcome with p-value 0.152 and 0.497 (p>0,05) respectively. Conclusions: There is a significant association between age and treatment outcome but no significant association between gender and comorbidity with treatment outcome. ABSTRAK Latar Belakang: Indonesia menduduki peringkat ke-2 dunia untuk kasus TBC dengan populasi kasus yang terus meningkat. Pada tahun 2018, Shorter Treatment Regimen (STR) diperkenalkan sebagai rejimen baru untuk mengobati pasien TB-MDR. Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor yang berkorelasi dengan hasil pengobatan pasien TB-MDR yang diobati dengan Regimen STR. Metode: Penelitian ini merupakan penelitian deskriptif-analitik dengan desain cross-sectional yang dilakukan di Rumah Sakit Adam Malik Medan. Subyek penelitian adalah 150 pasien TB Paru Resisten Obat di poliklinik TB MDR sesuai kriteria inklusi dan eksklusi. Hasil: Pasien TB-MDR yang diobati dengan STR sebagian besar berusia <50 tahun (65,2%) dan berjenis kelamin laki-laki sebanyak 107 subjek (70,4%). Mayoritas subjek dengan penyakit penyerta sebanyak 94 orang (61,8%); 43 orang (28,3%) DM, 5 orang (3,3%) CHF, 3 orang (2,0%) HIV, 1 orang (0,7%) DM & CHF, dan 1 orang (0,7%) DM & HIV. Hasil pengobatan adalah 47,4% sembuh, 6,6% gagal, 34,8% putus berobat dan 11,2% meninggal. Uji chi square dilakukan untuk menilai hubungan antara usia dengan hasil pengobatan dan didapatkan nilai p = 0,038 yang menunjukkan adanya hubungan yang signifikan namun berdasarkan jenis kelamin dan penyakit penyerta ditemukan nilai p masing-masing 0,152 dan 0,497 (p>0,05) yang menunjukkan tidak ada hubungan antara jenis kelamin dan penyakit penyerta terhadap hasil pengobatan. Kesimpulan: Terdapat hubungan yang signifikan antara usia dan hasil pengobatan namun tidak ada hubungan yang signifikan antara jenis kelamin dan penyakit penyerta dengan hasil pengobatan.